Meningkatkan Penguasaan Kosakata dan Pemahaman Teks Bahasa Arab Siswa melalui Penggunaan Aplikasi Assemblr Edu Berbasis Augmented Reality - Fauzia, Eva Lathifah; Abdul Aziz, Agus Umar (Tadris Al-’Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2024)
Vocabulary acquisition and reading comprehension in Arabic remain problematic for students, necessitating innovative teaching methods. One potential solution is using technology-based learning media, such as the Assemblr Edu app that utilizes Augmented Reality (AR). This study aims to evaluate the effectiveness of the Assembly Edu app, based on Augmented Reality, in enhancing vocabulary acquisition and reading comprehension in Arabic among eighth-grade students at MTsN 9 Majalengka. The research employs a quantitative and quasi-experimental method (non-equivalent group control design). Data were collected through observations, interviews, tests, questionnaires, and documentation. The analysis revealed that the average scores for vocabulary acquisition and reading comprehension increased from 45.45 to 58.40 after using the app, marking a 24% improvement. This significant increase indicates that the AR application effectively enhanced both aspects compared to the control class that did not use the app. The findings have important implications for Arabic language education in Indonesia, particularly in integrating technology to improve teaching effectiveness. Recommendations for future research include exploring AR applications across different educational levels, developing app features tailored to student needs, and conducting long-term studies and comparative evaluations with other teaching methods.